High‐throughput flow cytometry data normalization for clinical trials. Issue 3 (31st December 2013) - Finak, Greg; Jiang, Wenxin; Krouse, Kevin; Wei, Chungwen; Sanz, Ignacio; Phippard, Deborah; Asare, Adam; De, Stephen C.; Self, Steve; Gottardo, Raphael
Abstract Flow cytometry datasets from clinical trials generate very large datasets and are usually highly standardized, focusing on endpoints that are well defined apriori. Staining variability of individual makers is not uncommon and complicates manual gating, requiring the analyst to adapt gates for each sample, which is unwieldy for large datasets. It can lead to unreliable measurements, especially if a template‐gating approach is used without further correction to the gates. In this article, a computational framework is presented for normalizing the fluorescence intensity of multiple markers in specific cell populations across samples that is suitable for high‐throughput processing of large clinical trial datasets. Previous approaches to normalization have been global and applied to all cells or data with debris removed. They provided no mechanism to handle specific cell subsets. This approach integrates tightly with the gating process so that normalization is performed during gating and is local to the specific cell subsets exhibiting variability. This improves peak alignment and the performance of the algorithm. The performance of this algorithm is demonstrated on two clinical trial datasets from the HIV Vaccine Trials Network (HVTN) and the Immune Tolerance Network (ITN). In the ITN data set we show that local normalization combined with template gating can account for sample‐to‐sample variability as effectively as manual gating. In the HVTN dataset, it is shown that local normalization mitigates false‐positive vaccine response calls in an intracellular cytokine staining assay. In both datasets, local normalization performs better than global normalization. The normalization framework allows the use of template gates even in the presence of sample‐to‐sample staining variability, mitigates the subjectivity and bias of manual gating, and decreases the time necessary to analyze large datasets. © 2013 International Society for Advancement of Cytometry